Utilise e-commerce platforms to increase student and alumni entrepreneurship - Nor Salwana, Mohammad Idris (2021)
PAYA BESAR, 18 November 2021 – The opportunity for students and alumni to succeed in the field of entrepreneurship is enormous and brighter compared to 20 years ago with the rapid development of digital technology today.